Technologieorientierte Bahnplanung für die 3D-Laserstrahlbearbeitung - Backes, Frank (1997)
The aim of the research work was the development of an technology orientated path planning algorithm for 3D laser processing. The algorithm allows for an automatical off-line generation of machine programs for laser cutting and welding. Besides a CAD model of the workpiece a model of the robot is used, which represents the geometry and the kinematic properties of the robot. Programs can be created for gantries with 5 axes and robots with 6 rotational axes. By making use of path planning strategies, which were especially developed for 3D laser processing, optimised machine programs can be generated off-line with respect to path velocity and the dynamic behaviour of the robot. Since the time consuming teach-in procedure can be avoided, the algorithm leads to a significant reduction of the programming time and to an increased machine utilisation. The advantages of the algorithm have been demonstrated by performing several processing tasks. One typical example is the cutting of deep drawn sheet metal parts, as it is carried for prototype manufacturin